Nossa América interpela a Igreja - Oliveira, Pedro Assis Ribeiro de (Revista Eclesiástica Brasileira, 2007)
A importância sociológica da religião não se mede pelo número de seus adeptos, mas por sua capacidade de formar o “clima moral” da sociedade. A América Latina, constituída para ser economicamente explorada pelas metrópoles e ainda na periferia do sistema econômico mundial, vive hoje uma onda de participação política dos setores populares em busca de democracia e de uma outra AL possível. Esses sinais dos tempos interpelam a Igreja católica, onde a pastoral comprometida com os Direitos Humanos e com as lutas populares tem sido contestada por setores conservadores. O V CELAM reafirmará a participação da Igreja na construção desse novo “clima político”, ou se preocupará apenas em aumentar o número de seus membros? Abstract: The sociological significance of religion is not measured by the number of its followers but by its ability to produce a “moral climate” in society. Latin America, still on the periphery of the world economic system and constituted to be economically exploited by the metropolises is currently experiencing a wave of political participation on the part of the most popular sectors of society in search of real democracy and of other possibilities for Latin America. These signsofthetimes are challenging the Catholic Church where the pastoral committed to the popular struggle and to Human Rights is being contested by the conservative sectors. Will the 5th Latin American Episcopal Conference (CELAM) reaffirm the Church’s participation in the construction of this new “political climate” or will it only be concerned with expanding its membership?